Konsep Pemikiran Muhaimin Iqbal tentang Mata Uang Dinar - Ariska Ariska; Muzdalifah Muhammadun (Institut Agama Islam Negeri Parepare, 2022)
The dinar currency is a medium of exchange that has been enforced or used since the time of the Prophet Muhammad. and is a currency that has been recognized and has never experienced inflation as happened to paper currency. The value of the rupiah currency is currently experiencing a decline in value even now the dollar value is very high, amounting to Rp. 14,000 per one dollar when converted into rupiah. Due to the unstable currency value, the level of the country's economy also feels the impact. The objectives to be achieved in this research are : first, knowing the genealogical background of Muhaimin Iqbal's thoughts. second, knowing the dinar currency according to Islam, and third, knowing the concept of Muhaimin Iqbal's thoughts about the dinar currency. The type of research used by the author is this type of research, including library research. The data collection technique was carried out starting from reading some guides or references and then sorting it out so that conclusions were obtained as answers to the questions listed in the problem formulation. The results of this study indicate that, Muhaimin Iqbal is a practitioner, economist and thinker in Indonesia. He has also written and published several books of his own writing. He is also an entrepreneur who founded several companies including dinar outlets which we can access through the website outletdinar.com. Honey House, and Daarul Muttaqin Entrepreneurial Islamic Boarding School (Jonggol Farm). Second, the dinar currency according to Islam. According to Muhaimin Iqbal, the dinar currency is a currency whose value stability has been proven and can prosper the community. He himself has set up a dinar-based website where people can discuss questions and find out more about the dinar currency. This dinar currency can prevent inflation due to its stable value.